Psychosocial Relationship with Sexual Consent Behavior of the Main Female Character in the Novel “Amba” - Nafia, Hayya; Puspitasari, Nur Aini (Universitas Muhammadiyah Malang, 2023)
Patriarchal stigma restricts women from sexual desires that are synonymous with naughty and taboo. However, sexuality is a crucial aspect of human identity and involves ethical consent behavior. It is important to consider the responsibility of adult independence and the challenges that teenagers face in their self-discovery process, as influenced by Erikson's psychosocial development theory. The goal of this research is to connect psychosocial behaviour with women's sexual consent in the novel Amba. Amba is a courageous woman who makes intimate decisions despite facing stereotypical obstacles. The researcher applied a literary psychology approach, incorporating Erikson's psychosocial theory and Shumlich and Fisher's qualitative descriptions of sexual consent expressions. The way of collecting data involves reading the novel objects, marking the findings of the relationship between the data variables, and further interpreting the results of the analysis in the process of reduction, presentation, and conclusion as a data analysis technique. The research reveals that Amba's curious spirit came from her upbringing with patriarchal stereotypes, being a firstborn, and the unknown nature of the outside world. Amba recognizes her own desires in a consensual sexual relationship, unaffected by societal restrictions. The decision to engage in sexual activity considers conscious awareness, motivation, and behavioural skills. This behaviour upholds the rights of women and men to vote. Successful accountability for these actions confirms a mature and responsible adult role. Throughout the research findings, the connection between sexual agreement and gender equality, as well as the potential for sexual violence as a meaningful reflection of life, is the key.